Microbiological quality of farm-reared freshwater fish, rohu (Labeo rohita) - Jeyasekaran, G; Ayyappan, S (Indian Journal of Fisheries, 2011)
The microbiological quality of farm-reared freshwater fish, rohu (Labeo rohita)stored at two different temperatures was studied. The fish fillet was found tohave an initial bacterial load of 103 /g. The initial level of lactics, staphylococci,aeromonads, anaerobes and molds in the fish fillet was 101/g. The vibrios andE. coli were initially absent, but Salmonella present. The fish fillet held atambient temperature (28 Â± 20C) was organoleptically acceptable up to 10 h,when total bacterial load was in the threshold of exceeding 106/g. However, thefish fillet stored at freezer temperatures (-10 to -150C) was found to be in acceptablecondition even after 30 days of storage and the total bacterial load wasfluctuating in the range of 103 - 104 / g. In the fish fillets stored at these twotemperatures, Staphylococcus sp. and Lactobacillus sp. were found to be thedominant microflora, although there was a shift in bacterial flora consisting ofBacillus, Micrococcus, Flavobacterium, Acinetobacter and Enterobacter duringstorage at low temperatures.